2013
DOI: 10.1007/s11239-013-0939-3
|View full text |Cite
|
Sign up to set email alerts
|

Prednisone versus high-dose dexamethasone for untreated primary immune thrombocytopenia. A retrospective study of the Japan Hematology & Oncology Clinical Study Group

Abstract: High-dose dexamethasone (HDD) has been shown to be an effective initial treatment for immune thrombocytopenia (ITP), but it is not clear whether HDD offers any advantages over conventional-dose prednisone (PSL). We retrospectively compared the efficacy and toxicity of HDD and PSL for newly diagnosed ITP. The response was evaluated according to the International Working Group (IWG) criteria. We analyzed data from 31 and 69 patients in the HDD and PSL groups, respectively. There were no significant differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…The ideal dose, regimen, and duration of treatment have not been well established. Several studies showed intermittent high dose dexamethasone treatment is more effective than the conventional, continuous administration of other forms of steroids . Long‐term remission has been reported in a significant number of patients although maintenance treatment was needed in some studies .…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The ideal dose, regimen, and duration of treatment have not been well established. Several studies showed intermittent high dose dexamethasone treatment is more effective than the conventional, continuous administration of other forms of steroids . Long‐term remission has been reported in a significant number of patients although maintenance treatment was needed in some studies .…”
Section: Discussionmentioning
confidence: 70%
“…Several studies showed intermittent high dose dexamethasone treatment is more effective than the conventional, continuous administration of other forms of steroids. [15][16][17][18] Long-term remission has been reported in a significant number of patients although maintenance treatment was needed in some studies. 17 Although the present research is not a randomized control study, it consists of a relatively large treatment cohort and, therefore, provides clinical evidence supporting steroids as the standard initial treatment of ITP.…”
Section: Discussionmentioning
confidence: 99%
“…13 Retrospective studies comparing the 2 approaches in smaller cohorts yielded conflicting results [14][15][16] ; thus, RCTs directly comparing these 2 corticosteroid regimens are required to provide higher level evidence of efficacy. The design of this study was based on the standardized definitions and outcome criteria of the IWG.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple small trials on prednisone and dexamethasone with various outcomes. [63][64][65][66][67][68][69] In a meta-analysis of high-dose dexamethasone vs prednisone, there was no difference in platelet count response at 6 months; however, high-dose dexamethasone led to faster responses without additional toxicity. 70 Acyclovir may be given with dexamethasone to minimize the potential for herpes virus reactivation (evidence level IV).…”
Section: Goals Of Therapymentioning
confidence: 99%